Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Pengambilan Keputusan Pembelian Pada PT Samawa Property Group Kabupaten Probolinggo - Haidiputri, Trivosa Aprilia Novadiani; Lidyana, Novita; Hidayati, Rr. Setyani (Universitas Panca Marga, 2024)
The purpose of this study was to determine the effect of product quality and service quality on housing purchase decisions at PT. Samawa Property Probolinggo. The population used from the results of this study are consumers who have bought a house at PT. Samawa Property Kabupaten Probolinggo , who is located Karanggeger totaling 52 people. The sampling technique has been carried out using saturated samples. The method of data analysis in this study uses descriptive analysis with a quantitative approach. The results of this study indicate that: (1) The test results show that product quality has a positive and significant effect on purchasing decision making at PT. Samawa Property Kabupaten Probolinggo; (2) service quality has a positive and significant effect on purchasing decision making at PT. Samawa Property Kabupaten Probolinggo; (3) product quality and service quality have a simultaneous effect on purchasing decision making at PT. Samawa Property Kabupaten Probolinggo; (4) product quality has a dominant effect on purchasing decision making at PT. Samawa Property Kabupaten Probolinggo